Generation of Common Marmoset Model Lines of Spinocerebellar Ataxia Type 3 - Tomioka, Ikuo; Nagai, Yoshitaka; Seki, Kazuhiko (Frontiers in Neuroscience, 2020)
Animal models are indispensable tools in the development of innovative treatments for rare and incurable diseases. To date, there is almost no effective treatment for neurodegenerative diseases, and model animals that properly simulate human disease pathologies are eagerly anticipated to identify disease biomarkers and develop therapeutic methods and agents. Among experimental animals, non-human primates are the most suitable model animals for the study of neurodegenerative diseases with human-specific higher brain dysfunction and late-onset and slowly progressing symptoms. With the rapid development of novel therapies such as oligonucleotide therapeutics and genome editing technologies, non-human primate models for neurodegenerative diseases will be essential for preclinical studies and active interventional trials. In a previous publication, we reported the generation of the first transgenic marmoset model of spinocerebellar ataxia type 3 and successful obtainment of subsequent generations with stable disease onset. Moreover, we generated transgenic marmosets in which the transgene was controlled by the tetracycline-inducible gene expression system. In this mini-review, we summarize the research on our marmoset model of spinocerebellar ataxia type 3.